1995
DOI: 10.1016/0014-5793(95)01008-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypoosmolality on the abundance, poly(A) tail length and axonal targeting of arginine vasopressin and oxytocin mRNAs in rat hypothalamic magnocellular neurons

Abstract: Arginine vasopressin (AVP) and oxytocin (OT) mRNAs are targeted to the axonal compartment of rat hypothalamic magnocellular neurons. Salt-loading results in a considerable rise in hypothalamic and axonal AVP mRNA but only a moderate increase for axonal OT mRNA. Here we report that hypoosmolality gives rise to a rapid decrease of axonal AVP encoding transcripts to undetectable levels after 2 weeks. The levels of OT mRNA in the axonal compartment did not change significantly. In the hypothalamus the mRNA for AVP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…AVP innervation to hippocampus originates mainly from the paraventricular nucleus of hypothalamus (PVN) [ 96 ] controlling the release of stress hormones. A possible source of increased level of Avp transcripts in the hippocampal tissue may be the axonal transport of mRNA from the PVN because Avp mRNA is up-regulated by stress in PVN [ 97 ] and is transported into axons [ 98 ]. Fabp7 gene encodes the brain fatty acid binding protein that regulates hippocampal functions such as neurogenesis and behavior [ 99 ] and may be associated with psychiatric disorders [ 100 , 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…AVP innervation to hippocampus originates mainly from the paraventricular nucleus of hypothalamus (PVN) [ 96 ] controlling the release of stress hormones. A possible source of increased level of Avp transcripts in the hippocampal tissue may be the axonal transport of mRNA from the PVN because Avp mRNA is up-regulated by stress in PVN [ 97 ] and is transported into axons [ 98 ]. Fabp7 gene encodes the brain fatty acid binding protein that regulates hippocampal functions such as neurogenesis and behavior [ 99 ] and may be associated with psychiatric disorders [ 100 , 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA poly(A) tail length of some secreted or transmembrane proteins is reported to change in several conditions. This is also true for neurohypophysial hormones, as follows: osmotic stimulus induced elongation of AVP and OT mRNA poly(A) tails, accompanied by increases in the mRNA expression in the SON (Carrazana et al 1988; Zigg et al 1988; Carter & Murphy, 1991); hyponatraemia induced shortening of the AVP and OT mRNA poly(A) tail (Chooi et al 1992; Svane et al 1995); and the circadian peak of AVP mRNA expression in the suprachiasmatic nucleus was accompanied by elongation of the AVP mRNA poly(A) tail length (Robinson et al 1988). These data suggest that the length of the poly(A) tail is a crucial determinant of AVP and OT mRNA stability.…”
Section: Effects Of Er Stress On Mrna Poly(a) Tail Lengthmentioning
confidence: 97%
“…Furthermore, AVP synthesis in magnocellular neurons as indicated by AVP mRNA levels is virtually turned off after 7 days of DDAVP treatment [16]. In addition, it has recently been found that also the axonal content of AVP mRNA is reduced in parallel [10]. However, basal plasma levels of AVP remain unchanged in hypoosmolar rats [8].…”
Section: Discussionmentioning
confidence: 99%
“…The control group consisted of rats implanted with vehicle-loaded pumps and submitted to the same diet as the DDAVP-treated rats plus water ad libitum. The hypoosmolality protocol used by us has been thoroughly evaluated elsewhere [10] including demonstration of a continuous weight gain after surgery similar to that observed in control rats.…”
Section: Methodsmentioning
confidence: 99%